2005
DOI: 10.1124/jpet.105.087908
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of N-Methyl-d-aspartate Receptors by Donepezil in Rat Cortical Neurons

Abstract: Nicotinic acetylcholine receptors and N-methyl-D-aspartate (NMDA) receptors are known to be down-regulated in the brain of patients with Alzheimer's disease. It was previously shown that the nootropic drugs nefiracetam and galantamine potentiate the activity of both nicotinic and NMDA receptors. We hypothesized that donepezil, a nootropic with a potent anticholinesterase activity, might also affect the NMDA system. NMDA-induced currents were recorded from rat cortical neurons in primary culture using the whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…It has been suggested that most AChE inhibitors available antagonize cerebral NMDA receptors with a potency of approximately three orders of magnitude lower than their action on AChE activity Moriguchi et al 2005;Muñez-Torrero and Camps 2006;Takada-Takatori et al 2006). Therefore, a possible beneficial effect of donepezil based on inhibition of excitotoxicity should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that most AChE inhibitors available antagonize cerebral NMDA receptors with a potency of approximately three orders of magnitude lower than their action on AChE activity Moriguchi et al 2005;Muñez-Torrero and Camps 2006;Takada-Takatori et al 2006). Therefore, a possible beneficial effect of donepezil based on inhibition of excitotoxicity should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of the differential effects of the compounds observed in our studies and the one cited above is unclear, although there are some differences in the pharmacology of these compounds (i.e., other than that related to AChEI activity) that may be of importance. For example, in culture studies, galantamine, has been observed to potentiate NMDA currents in rat cortical multipolar neurons (Moriguchi et al, 2005). In contrast, donepezil, potentiated NMDA receptors in both bipolar and multipolar neurons, but its effects on multipolar neurons were biphasic.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of donepezil has been found to increase levels of norepinephrine, dopamine, and serotonin, in addition to its effects on acetylcholine (Cuadra et al, 1994;Giacobini et al, 1996;Shearman et al, 2006). Donepezil also has been shown to potentiate NMDAinduced currents in multipolar and bipolar neurons (Moriguchi et al, 2005), as well as to produce NMDA receptor blockade and have agonist-like activity at sigma receptors (Maurice et al, 2006). Rimonabant is thought to produce its effects by either antagonizing a tonically active endogenous cannabinoid system or through its actions as an inverse agonist (Landsman et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been suggested that mechanisms other than enhancement of cholinergic function may be involved in the pharmacology of donepezil efficacy in improving cognition (Narahashi et al, 2004;Moriguchi et al, 2005). Systemic administration of donepezil has been found to increase levels of norepinephrine, dopamine, and serotonin, in addition to its effects on acetylcholine (Cuadra et al, 1994;Giacobini et al, 1996;Shearman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%